Pemberdayaan Kaum Ibu melalui Solidaritas Bantuan Pangan pada Masa Pandemi Covid-19 di Wilayah Perumahan Kota Bekasi - Sri Rijati Wardiani; Tania Intan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2021)
The Covid-19 pandemic, which is a global disaster, has had an impact on various aspects of people's lives. Housewives can be considered as those who are experiencing the most difficulties due to the pandemic because they must continue to manage and maintain their health in the middle of limitations. This community service activity is aimed at helping and empowering mothers as a form of solidarity with residents in the East Bekasi city area. The form of activity carried out is social assistance in the form of providing food and necessities regularly every Friday since December 2019 until now. All activities are carried out by implementing and implementing health protocols. The results of the activity show that there are benefits for various parties, ranging from donors, aid recipients, vegetable traders, and small grocery stores. This activity is also a form of citizen participation in helping the government to alleviate poverty and economic difficulties due to the pandemic. Assistance in the form of food and basic needs supports increasing the nutritional intake of the family so that it can maintain the immunity of the residents who get it. It is hoped that similar activities can be carried out consistently, in bulk, and evenly, in other places so that the results have a more tangible impact.